STUDY OF MICROMYCETES OF THE GENUS TRICHODERMA FOR ANTAGONISM TO FUSARIUM SP. FROM POTATOES AFFECTED BY DRY ROT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In order to develop a biofungicide against potato Fusarium, 12 micromycetes of the genus Trichoderma isolated from various wood fungi were tested for antagonism to Fusarium sp. Fusarium was isolated from potatoes affected by dry rot. To determine the antagonism of each trichoderm isolate to fusarium, the method of “double cultures” was used - growing trichoderm together with fusarium in Petri dishes on agar. Fast-growing and suppressing Fusarium sp. trichoderm isolates were identified.
Keywords: antagonism; pathogen; Trichoderma; Fusarium